The impact of new technologies (AI, Blockchain & Big Data) in the accounting profession - Hasan, Zulkifli; Che Hassan, Nor Asmawani (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
The adoption of new technologies such as Artificial Intelligence, Blockchain and Big Data will bring an advancement and improvement to the accounting field, but it will also raise some issues that the accountant must face. One of the major issues resulting from the adoption of new technology is job displacement. The need for traditional accounting-related employment will decline as AI systems become increasingly capable of handling more mundane activities like data entry, transaction processing, and even simple audits. Furthermore, the implementation of blockchain technology raises concerns about data privacy, the irreversibility of errors, and the misuse of private information even as it improves transaction security and transparency. Moreover, the reliance on AI and Big Data analytics introduces concerns about algorithmic bias, inaccuracies, and the ethical use of data. All these new technologies require accountants to have a significant amount of skill set to optimize the system. As the profession is getting restructured into a digital system, the demand for those professionals is rising who can interpret Big Data analytics and other technologies to provide strategic insights. This transition from traditional accounting methods to new digital methods poses a threat to the accountants that do not want to embrace these new systems because they do not want to leave the comfort zone. If the accountants fail to embrace these new technologies into their accounting skill set, they will fall behind their competitors and miss out on many opportunities that can grow their career in the profession. This paper explores the implications of these technologies on the accounting profession, discussing both the benefits and the potential pitfalls that need to be navigated for a balanced integration.